Primary psychiatric conditions: Dermatitis artefacta, trichotillomania and neurotic excoriations - Jillian W Wong; Tien V Nguyen; John YM Koo (Wolters Kluwer Medknow Publications, 2013)
Primary psychiatric conditions encountered in dermatology include dermatitis artefacta, trichotillomania (TTM) and neurotic excoriations. For these disorders, the primary pathologic condition involves the psyche; therefore, any cutaneous findings are self-induced. Herein, we review common primary psychiatric conditions in dermatology - dermatitis artefacta, neurotic excoriations and TTM - and examine their epidemiology, clinical presentation, differential diagnosis and treatment strategies. For all primary psychiatric disorders, the most effective underlying strategy is to first establish a strong therapeutic rapport with the patient. Various pharmacologic and non-pharmacologic therapies can then be attempted afterwards to successfully manage these patients.